SIMBOL ORDO ILLUMINATI DALAM KEHIDUPAN SOSIO KULTURAL MUSLIM DI ARAB SAUDI: ANALISIS SEMIOTIK SIMBOLIK - Ani Choirun Nisa, M. Farkhan M (Center of Middle Eastern Studies (CMES): Jurnal Studi Timur Tengah, 2016)
Illumination Ordo is one of the international secret organization. The aim of this organization is to build a new world arrangement which has a significant role in several countries. And Saudi Arabia is one of those countries.This study discussed the history factors that lie behind the phenomenon of the use of Ordo Illuminati symbols by moslem in Saudi Arabia and Aspects of life that associated with the use of Ordo Illuminati symbols in Saudi Arabia.The method of this study was descriptive qualitative by using library research technique which followed 4 steps; they are: (1) making a research plan, (2) collecting the data, (3) analyzing the data, (4) and writing the report. Moreover, the theory used in this study was semiotic symbolic which is proposed by Charles Sander Pierce. Based on this study, there are two conclusions; they are: (1) the history factor that lie behind the phenomenon of the use of Ordo Illuminati symbols by moslem in Saudi Arabia. (2) Aspects of life that associated with the use of Ordo Illuminati symbols in Saudi Arabia.